Phylogeny and classification of the New World suboscines (Aves, Passeriformes) - Ohlson, Jan I.; Irestedt, Martin; Ericson, Per G. P.; Fjeldså, Jon (Zootaxa, 2013)
Here we present a phylogenetic hypothesis for the New World suboscine radiation, based on a dataset comprising of 219 terminal taxa and five nuclear molecular markers (ca. 6300 bp). We also estimate ages of the main clades in this radiation. This study corroborates many of the recent insights into the phylogenetic relationships of New World suboscines. It further clarifies a number of cases for which previous studies have been inconclusive, such as the relationships of Conopophagidae, Melanopareiidae and Tityridae. We find a remarkable difference in age of the initial divergence events in Furnariida and Tyrannida. The deepest branches in Furnariida are of Eocene age, whereas the extant lineages of Tyrannida have their origin in the Oligocene. Approximately half of the New World suboscine species are harboured in 5 large clades that started to diversify around the Mid Miocene Climatic Optimum (16–12 Mya). Based on our phylogenetic results we propose a revised classification of the New World suboscines. We also erect new family or subfamily level taxa for four small and isolated clades: Berlepschiinae, Pipritidae, Tachurididae and Muscigrallinae.